The Role of E-Service Quality and Brand Image on Purchase Intention of Smartphone Products - Utomo, Sulistyo Budi; Setiadi, Bekti; Astuti, Enny Diah; Wahyuningratna, Ratu Nadya; Hendra, Hendra; Nusyirwan, Nusyirwan (Malikussaleh University, Aceh, Indonesia, 2025)
The smartphone industry has witnessed remarkable growth over the past decade, becoming one of the most dynamic and competitive markets globally. With technological advancements and increasing internet penetration, consumers increasingly rely on e-commerce platforms to purchase smartphones. Consequently, the quality of e-services provided by companies has emerged as a critical determinant of consumer purchase behaviour. Simultaneously, brand image remains a key factor influencing consumer preferences and loyalty. This study investigates the impact of e-service quality and brand image on consumers' purchase intentions for smartphone products. In an era where online shopping has become a dominant trend, understanding how these factors influence consumer behaviour is crucial for businesses seeking a competitive edge. Data for this research was collected from 100 respondents using structured questionnaires, and multiple regression analysis was employed to assess the relationships between the variables. The findings reveal that e-service quality and brand image significantly positively affect purchase intention. High-quality e-services, characterized by website functionality, responsiveness, and security, enhance consumer trust and encourage purchasing decisions. Simultaneously, a strong brand image fosters consumer loyalty and preference, further amplifying purchase intention. Moreover, the interplay between e-service quality and brand image shows a synergistic effect, where combining both factors results in even higher purchase intention. This research underscores the importance of seamless online experiences and robust branding strategies for companies operating in the smartphone market. Practical implications include businesses needing to continually improve their e-service platforms by investing in user-friendly designs, efficient customer service, and secure transaction systems. Maintaining a consistent and appealing brand image through targeted marketing and corporate social responsibility initiatives is critical. These efforts attract new customers and retain existing ones, driving long-term success in the competitive landscape of smartphone products. By addressing both e-service quality and brand image, companies can effectively influence consumer behaviour, enhance satisfaction, and foster brand loyalty.